TALK LIKE A PRO: BOOTCAMP OF ENGLISH PUBLIC SPEAKING FOR GEN Z AT SMA RU 2 GONDANGLEGI MALANG - Muyassaroh (JIK-PkM: Jurnal Inovatif dan Kreatif hasil Pengabdian kepada Masyarakat, 2026)
This Community Service Program aims to enhance the English public-speaking skills and self-confidence of Gen Z students at SMA RU 2 through the “Talk Like a Pro” bootcamp. The main challenges addressed include students’ low confidence in speaking English and the lack of engaging, culturally relevant practice media in the pesantren environment. The program was implemented through intensive training sessions consisting of basic public-speaking instruction, guided practice, ice-breaking activities, and assisted production of short English videos featuring unique santri characteristics. The results show a clear improvement in students’ willingness to speak, classroom participation, and creativity in expressing Islamic messages and daily pesantren life through short-form video content. The final videos serve not only as an assessment tool for speaking skills but also as positive digital content that can support the school’s branding efforts. Overall, the bootcamp proved effective and has strong potential for further development, particularly by extending mentoring duration and diversifying materials to suit the needs of digital-native learners.